ANALISIS PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) PADA LAPORAN KEBERLANJUTAN PERUSAHAAN PERBANKAN DI INDONESIA YANG TERDAFTAR DI BEI PADA TAHUN 2024 - Ananda Eka Agustina; Jeselin Devi Adesya Felandy; Titiek Rachmawati (STKIP Subang, 2026)
This study is motivated by the increasing demand for sustainability transparency and the importance of Environmental, Social, and Governance (ESG) disclosure as part of corporate accountability, particularly in the banking sector. This study aims to analyze the level of ESG disclosure in banking companies listed on the Indonesia Stock Exchange in 2024. The research employs a quantitative descriptive approach using content analysis techniques on sustainability reports and annual reports of four banks, namely Bank Central Asia, Bank Rakyat Indonesia, Bank Negara Indonesia, and Bank Mandiri. Measurement is conducted using ESG indicators based on the Global Reporting Initiative (GRI) with a dichotomous scoring technique, calculated in the form of a percentage index. The results indicate that the level of ESG disclosure across all companies falls into the high category, with index values ranging from 86.7% to 90.0%. The governance dimension exhibits the highest level of disclosure, followed by the social dimension, while the environmental dimension shows a relatively lower level of disclosure. These findings suggest that banking companies in Indonesia have demonstrated good ESG transparency; however, further strengthening in the environmental aspect is still required to achieve a more balanced and comprehensive ESG disclosure.